Promoting moral and democratic competencies: towards an educational turn of Bioethics - Serodio, Aluisio; I. Kopelman, Benjamin; Bataglia, Patricia U.R. (Revista Bioética, 2016)
The purpose of this paper is to present Bioethics, particularly its educational aspect, as a way to promote moral and democratic competencies, thus improving a personal capacity to face not only bioethical issues but also broader ethical, moral and even political problems. We believe that we should invest educative efforts on the affective and cognitive aspects of moral behavior if we want to promote the capacity to make moral judgments and act according to them. In pluralistic democratic societies, it is necessary to also promote the capacity to speak up and listen to arguments as a means to deal with moral problems. Any Bioethics which does not also include an educational action is prone to lose most of its significance. We propose that Bioethics should be led to an educational turn, focusing on the construction of an educative toolbox composed of interventional and evaluative instruments.